Factors Affecting Library Profession and Professional Image of Sri Lankan Librarians:An Overview - Weerasooriya, W. A. (Journal of Information and Knowledge, 2016)
Image of a profession is a significant area of interest. Substantial amount of literature has appeared on this subject, both in the West and the East. It is important to study the professional image of Sri Lankan Librarians in a rapidly changing social, economic, political and ICT environment. The principal objective of this study is to study the image of Sri Lankan library professionals. The other objectives are to explore what is professional image, to examine the mechanism and environmental factors affecting the professional image of Sri Lankan Librarians, to investigate the mindsets and personal and professional factors affecting the image of Sri Lankan librarians, to identify the obstacles and hindrances facing Sri Lankan library profession and professionals and finally to design and present a model for developing image of librarians and the library profession of Sri Lanka. The study is scrutinized with a proactive approach and it is not the intention to pass any sarcastic criticism against the profession or professionals.